PERJANJIAN SEWA MENYEWA LAHAN DI DESA SUNGAI PURUN BESAR PRESPEKTIF KOMPILASI HUKUM EKONOMI SYARIAH BAB XI TENTANG IJARAH - Muhammad Husni; Abu Bakar; Husnun Nahdhiyyah (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2025)
The objective of this research is to examine: 1) The implementation of agricultural land lease agreements in Sungai Purun Besar Village, Mempawah; and 2) The practice of such leases from the perspective of the ijarah contract under the Compilation of Sharia Economic Law (KHES). The researcher employed a qualitative research method. Data collection techniques included observation, interviews, and documentation. For data analysis, the researcher conducted data verification, tabulation, reconstruction, and systematic organization. The findings indicate that: 1) The implementation of agricultural land lease agreements in Sungai Purun Besar Village, Mempawah Regency, can be observed through three aspects: the contract itself, the object of the contract, and the rental payment arrangement agreed upon by both the landowner and the land manager. The contract used is an oral ijarah agreement. The object of the contract in this study is agricultural land. Rental payments are made after harvest, according to prior mutual agreement based on the size of the leased land. 2) The implementation of agricultural land leasing in Sungai Purun Besar Village, viewed from the perspective of the ijarah contract, complies with KHES provisions regarding the pillars (rukun) of ijarah, the form of contract (sighat), conditions for execution, rental payment mechanisms, use of the leased object, rental price, type of ma’jur (lessee), and return of the land. These practices are consistent with KHES regulations.